Obesity as a Risk Factor of Cancer - Theodore Dharma Tedjamartono; Ketut Suastika (MEDICINUS, 2026)
The prevalence of overweight and obesity continues to increase globally. These conditions are considered a serious public health concern due to its correlation with other diseases, such as type 2 diabetes mellitus, cardiovascular disease, andcancer. Obesity is defined as the accumulation of abnormal or excessive body fat that can impair health. Although obesity is not considered a major risk factor for cancer, it is associated with several types of cancer. One of the key mechanismsunderlying the relationship between obesity and cancer is chronic inflammation. In individuals with obesity, hypoxia can occur in adipose tissue, triggering alterations in leptin levels, dysregulation of adiponectin, macrophage infiltration, mitochondrial dysfunction, and an increased endoplasmic reticulum (ER) stress response. These changes collectively contribute to a state of chronic inflammation. Chronic inflammation is a mediator of cancer cell development, primarily by inducing changes in the tumor microenvironment and promoting the formation of cancer phenotypes (tumorigenesis). Other factors that explain the relationship between obesity and cancer in general will be explained in this literature review.